Design, synthesis, in vitro and in vivo evaluation of heterobivalent SiFAlin-modified peptidic radioligands targeting both integrin αvβ3 and the MC1 receptor: suitable for the specific visualization of melanomas? - Cheng, Xia; Hübner, Ralph; Kiedrowski, Valeska von; Fricker, Gert; Schirrmacher, Ralf; Wängler, Carmen; Wängler, Björn (Pharmaceuticals, 2021)
Combining two peptides addressing two different receptors to a heterobivalent peptidic ligand (HBPL) is thought to enable an improved tumor-targeting sensitivity and thus tumor visualization, compared to monovalent peptide ligands. In the case of melanoma, the Melanocortin-1 receptor (MC1R), which is stably overexpressed in the majority of primary malignant melanomas, and integrin αvβ3, which is involved in lymph node metastasis and therefore has an important role in the transition from local to metastatic disease, are important target receptors. Thus, if a radiolabeled HBPL could be developed that was able to bind to both receptor types, the early diagnosis and correct staging of the disease would be significantly increased. Here, we report on the design, synthesis, radiolabeling and in vitro and in vivo testing of different SiFAlin-modified HBPLs (SiFA = silicon fluoride acceptor), consisting of an MC1R-targeting (GG-Nle-c(DHfRWK)) and an integrin αvβ3-affine peptide (c(RGDfK)), being connected by a symmetrically branching framework including linkers of differing length and composition. Kit-like 18F-radiolabeling of the HBPLs 1-6 provided the labeled products [18F]1-[18F]6 in radiochemical yields of 27-50%, radiochemical purities of ≥95% and non-optimized molar activities of 17-51 GBq/μmol within short preparation times of 25 min. Besides the evaluation of radiotracers regarding logD(7.4) and stability in human serum, the receptor affinities of the HBPLs were investigated in vitro on cell lines overexpressing integrin αvβ3 (U87MG cells) or the MC1R (B16F10). Based on these results, the most promising compounds [18F]2, showing the highest affinity to both target receptors (IC50 (B16F10) = 0.99 ± 0.11 nM, IC50 (U87MG) = 1300 ± 288 nM), and [18F]4, exhibiting the highest hydrophilicity (logD(7.4) = −1.39 ± 0.03), were further investigated in vivo and ex vivo in a xenograft mouse model bearing both tumors. For both HBPLs, clear visualization of B16F10, as well as U87MG tumors, was feasible. Blocking studies using the respective monospecific peptides demonstrated both peptide binders of the HBPLs contributing to tumor uptake. Despite the somewhat lower target receptor affinities (IC50 (B16F10) = 6.00 ± 0.47 nM and IC50 (U87MG) = 2034 ± 323 nM) of [18F]4, the tracer showed higher absolute tumor uptakes ([18F]4: 2.58 ± 0.86% ID/g in B16F10 tumors and 3.92 ± 1.31% ID/g in U87MG tumors; [18F]2: 2.32 ± 0.49% ID/g in B16F10 tumors and 2.33 ± 0.46% ID/g in U87MG tumors) as well as higher tumor-to-background ratios than [18F]2. Thus, [18F]4 demonstrates to be a highly potent radiotracer for the sensitive and bispecific imaging of malignant melanoma by PET/CT imaging and impressively illustrates the suitability of the underlying concept to develop heterobivalent integrin αvβ3- and MC1R-bispecific radioligands for the sensitive and specific imaging of malignant melanoma by PET/CT.